ERRα promotes glycolytic metabolism and targets the NLRP3/caspase-1/GSDMD pathway to regulate pyroptosis in endometrial cancer - Pingping Su; Xiaodan Mao; Jincheng Ma; Lixiang Huang; Lirui Yu; Shuting Tang; Mingzhi Zhuang; Zhonglei Lu; Kelvin Stefan Osafo; Yuan Ren; Xinrui Wang; Xite Lin; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Tumor cells can resist chemotherapy-induced pyroptosis through glycolytic reprogramming. Estrogen-related receptor alpha (ERRα) is a central regulator of cellular energy metabolism associated with poor cancer prognosis. Herein, we refine the oncogenic role of ERRα in the pyroptosis pathway and glycolytic metabolism. Methods The interaction between ERRα and HIF-1α was verified using co-immunoprecipitation. The transcriptional binding sites of ERRα and NLRP3 were confirmed using dual-luciferase reporter assay and cleavage under targets and tagmentation (CUT&Tag). Flow cytometry, transmission electron microscopy, scanning electron microscopy, cell mito stress test, and extracellular acidification rate analysis were performed to investigate the effects of ERRα on the pyroptosis pathway and glycolytic metabolism. The results of these experiments were further confirmed in endometrial cancer (EC)-derived organoids and nude mice. In addition, the expression of ERRα-related pyroptosis genes was analyzed using The Cancer Genome Atlas and Gene Expression Omnibus database. Results Triggered by a hypoxic microenvironment, highly expressed ERRα could bind to the promoter of NLRP3 and inhibit caspase-1/GSDMD signaling, which reduced inflammasome activation and increased pyroptosis resistance, thereby resulting in the resistance of cancer cells to cisplatin. Moreover, ERRα activated glycolytic rate-limiting enzyme to bridge glycolytic metabolism and pyroptosis in EC. This phenomenon was further confirmed in EC-derived organoids and nude mice. CUT & Tag sequencing and The Cancer Genome Atlas database analysis showed that ERRα participated in glycolysis and programmed cell death, which resulted in EC progression. Conclusions ERRα inhibits pyroptosis in an NLRP3-dependent manner and induces glycolytic metabolism, resulting in cisplatin resistance in EC cells.